Comparing Project-Based Collaborative Networks for BIM Implementation in Public and Private Sectors: A Longitudinal Study in Hong Kong. (22nd August 2019) - Tang, Yixuan; Wang, Guangbin; Li, Heng; Cao, Dongping; Li, Xiaoying
Abstract : Due to the great potential of building information modelling (BIM) to address traditional design and construction problems, the governments in many regions, such as Hong Kong, have released related policies to advocate the use of BIM in public projects in recent years. Therefore, BIM might advance differently in the public and private sectors in these regions. Using the social network perspective and a longitudinal data set on BIM-based construction projects in Hong Kong from 2002 to 2017, this study quantitatively characterizes how the structural characteristics of the project-based collaboration networks for BIM implementation in the public (PUCN) and private sectors (PRCN) evolve differently over time. The empirical results provide evidence that both PUCN and PRCN have become increasingly dense and developed around some "centered" nodes during the examined period. However, it is revealed that PUCN exhibits a more significant trend in network closeness and centralization. Through characterizing the "centered" nodes individually, the results also reveal that local owner organizations generally play more active roles in PUCN, while local design and construction organizations generally play more actively in PRCN. The results also provide evidence that the evolution of the two networks closely relate to each other, with the design and construction organizations involved in PUCN during early periods significantly influencing the evolution of PRCN in the later periods. The findings not only provide a dynamic network view of how industry organizations interact with each other in BIM implementation practices across different types of projects but also provide insights into how relationship networks can be managed to facilitate the diffusion of innovations in the construction industry.